(untitled) (Advancements in Homeopathic Research, 2025)
Exfoliative dermatitis, also known as Erythroderma, is a severe and life-threatening condition that presents with diffuse erythema & scaling of the skin. It is one the uncommon skin disease conditions affecting both males & females and almost all age groups. Therapies like corticosteroids, anti-histamines & immunosuppressant/immunomodulatory medications are generally used to treat exfoliative dermatitis. However, these therapies only give symptomatic relief, not permanent disease improvement. In homoeopathy, there is a lot of literature regarding treating different skin diseases, such as exfoliative dermatitis. This article illustrates a documented case report of a patient with exfoliative dermatitis. In this particular case, exfoliative dermatitis condition is treated by Sulphur, based on the constitutional totality of the patient. The improvement was documented by proper treatment interpretation and photographic evidence during follow-up.[1]